E-Learning System in School Learning Process Using Agile Method: Case Study of SMK It Umamul Huda Malangbong - Fadilah, Winda Husnul; Suherman, Asep; Fahmi, Miftah; Latif, Dadang; Parghani, Rizal (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This research intends to design and execute a web-based e-learning system utilizing the Agile methodology at SMK IT Umamul Huda Malangbong. E-learning is an excellent means of enhancing the flexibility and efficiency of the educational process in schools. This system incorporates interactive elements, including online examinations, live chat, real-time notifications, and an intuitive UI, all intended to satisfy user requirements effectively. The Agile methodology employs an iterative approach, wherein the development process is executed over several cycles of planning, development, testing, and assessment. Each iteration is modified according to user feedback, yielding a pertinent and practical system. The test findings utilizing the Black Box approach indicate that this system operates effectively and satisfies the standards for reliability, validity, and compatibility for application in the SMK IT Umamul Huda Malangbong learning environment. The system's adoption necessitates training for teachers and students to guarantee a comprehensive understanding of its usage. The beneficial effects of e-learning adoption encompass enhanced accessibility, improved efficiency in assessment, and the facilitation of real-time communication between educators and learners. This technology markedly enhanced student engagement in educational activities, particularly during online examinations and debates. Other obstacles were identified, including inadequate internet infrastructure and user acclimatization to novel technologies. The adopted solutions encompassed collaboration with local internet service providers and the provision of alternative offline access to educational content. The study's results indicate that the web-based e-learning system effectively addressed the educational requirements of SMK IT Umamul Huda Malangbong and positively impacted the quality of education. This study advocates for advancing system integration with mobile devices and learning analytics to enhance user experience and overall learning efficacy.